THE PRACTICAL ISSUES BEHIND THE USE OF SOCIAL TECHNOLOGIES FOR THE IMPROVEMENT OF THE QUALITY OF LIFE OF ELDERLY PEOPLE IN THE CITY OF ALMATY - Akanova, A.A.; Kurmanova, G.M.; Abzaliyeva , S.A.; Akanova, K.K. (Interdisciplinary Approaches to Medicine, 2022)
Increasing amount of retired people represents one of the main challenges in social policy in the city of Almaty. Akimat developed and introduced a roadmap “Active Ageing” as a part of “The year of aged people support’, which underlined opening the first and a pilot center for retired people. Public Fund “Kumis Khasyr” developed and introduced a multidisciplairy program for the provision of a range of social services such as medical, social, pedagogical, educational, cultural.Under this program, 9,139 retired people were covered. Moreover, according to feedback 68% considered the overall organization good, 23% considered very good. Proper analysis on the needs showed that the main problems of the retirement age are social isolation, poor health, ageism, computer illiteracy, age-associated psycho-emotional disturbances such as anhedonia, depression, constantly emerging anxiety, panic attacks, as well as an extremely low level of cultural behavior. All of the above problems strongly suggest that there is a need to improve the policy of supporting an elderly person in the city of Almaty